2023
DOI: 10.1186/s13741-023-00297-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of remote ischaemic preconditioning on outcomes following non-cardiac non-vascular surgery: a systematic review and meta-analysis

Abstract: Background Remote ischaemic preconditioning (RIPC) has been investigated as a simple intervention to potentially mitigate the ischaemic effect of the surgical insult and reduce postoperative morbidity. This review systematically evaluates the effect of RIPC on morbidity, including duration of hospital stay and parameters reflective of cardiac, renal, respiratory, and hepatic dysfunction following non-cardiac non-vascular (NCNV) surgery. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Therefore, effective techniques to reduce adverse complications have important clinical significance to patients undergoing TAVR. RIPC originated from laboratory studies and was gradually applied to clinical trials, as RIPC could decrease inflammation and oxidative stress, providing a protective effect on many vital organs 41–49 77–84. RIPC was also performed in TAVR, as a non-invasive, easily feasible technique 51–54.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, effective techniques to reduce adverse complications have important clinical significance to patients undergoing TAVR. RIPC originated from laboratory studies and was gradually applied to clinical trials, as RIPC could decrease inflammation and oxidative stress, providing a protective effect on many vital organs 41–49 77–84. RIPC was also performed in TAVR, as a non-invasive, easily feasible technique 51–54.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies investigating the efficacy of RIPC on lung protective effects, such as the measurement of lung-specific biomarkers or collecting samples from bronchoalveolar lavage fluid, should be conducted. Likewise, studies examining other protective effect of RIPC on non-lung organ such as kidney or brain and its impact on mortality or hospital stay are needed because past studies including systematic review presented inconsistent results or indicated inconclusiveness 89 91 .…”
Section: Discussionmentioning
confidence: 99%